PSIKOEDUKASI PENINGKATAN KESEHATAN MENTAL PADA REMAJA DENGAN AUTOIMUN (KOMUNITAS ODAI) - Agustina Agustina; Azriel Benedict; Aufi Azzahra; Nilam F. F Hia (PROSIDING SERINA, 2021)
Autoimmune disease is a disease that occurs when the body's immune system attacks healthy cells in its own body. The danger is that this autoimmune disease can damage tissue cells in the body and cause inflammation and lead to serious conditions for sufferers, such as disorders of the bones, joints, nerves, glands, and other important organs. With a body condition where the immune system attacks the body's tissue and organ systems, people with autoimmune disease can experience various and complex physical and psychological problems. Autoimmune sufferers who are at the stage of adolescent development, will face various challenges related to the challenges of late adolescent developmental tasks towards early adulthood which can cause these adolescents to experience mental health problems. This limited physical condition due to immunity problems also hinders the activities and productivity of teenagers who are in their peak period of exploring various possibilities for their future. On the one hand, their mental health conditions can be disrupted due to physical limitations due to autoimmune, but on the other hand, they really need to maintain mental health in order to avoid stress that can cause them to relapse. Thus, it is necessary to take preventive measures to address the need to maintain mental health for adolescents with autoimmune disease in the Autoimmune People Community (ODAI). The PKM team provides psychoeducation to these teenagers with autoimmune on how to recognize the problems they face and ways to help improve their mental health.